NEODYMIUM CUPRATE SOLID SOLUTION SUBSTITUTIONS OF SUBMICRON DISPERSION: DOI: https://doi.org/10.17721/1728-2209.2020.1(57).3 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2020)
High-temperature superconducting compounds based on rare-earth elements with a perovskite-like structure play an important role in the creation of modern functional materials with special magnetic, superconducting and electrophysical properties. The potential of high-temperature superconducting compounds is widely used in microelectronics, medicine, transport, telecommunications technology, energy and more. Increased functionality, performance and reliability are the driving force for the production, research and application of this class of inorganic functional materials. Solid solutions of the type NdBa2–xNdxCu3O7–d, are structural analogues of HTSC cuprate YBa2Cu3Oy (Y123). The study of the substitution of Ba2+ atoms for Nd3+ is important for obtaining new promising materials with various electrophysical and magnetic properties, as well as improving the characteristics of existing substances. Compounds of the composition NdBa2-xNdxCu3O7–d, where x = 0–0.9 were synthesized sol-gel method. The parameters of the crystallattice and the transition temperature to the superconducting state for the synthesized compounds are calculated. The dependence of the parameters and the type of symmetry of the crystallattice of systems on the degree of substitution of x is investigated. It was found that the samples, sol-gel method are single-phase. The unsubstituted sample of NdBa2-xNdxCu3O7–d, is single-phase, has an orthorhombic syngony of o-Nd123 and a space group Pmmm. Within creasing degree of substitution x in solid solutions of NdBa2–xNdxCu3O7–d, where x = 0–0.9, there is a transition from the orthorhombic to tetragonal phase (space symmetry group P4/mmm).
Keywords: superconducting compounds; sol-gel synthesis method; critical temperature